The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s10811-020-02145-w
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical composition of red, green and brown seaweeds on the Swedish west coast

Abstract: Seaweed biomass has the potential to become an important raw material for bio-based production. The aim of this study was to screen the overall composition of several seaweed species on the Swedish west coast, including some scarcely studied species, to provide fundamentals for evaluation of biorefining potential and to benchmark with already potentially industrially relevant species and commercially important land-based biomasses. Twenty-two common seaweed species (green, red, brown) were collected and the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 57 publications
(67 reference statements)
21
39
0
1
Order By: Relevance
“…The lipid and ash content of F. vesiculosus and C. tomentosum agree generally with that described in the literature [56,[58][59][60][61]. The lipid content found in this work was 3.4 ± 0.5 and 2.2 ± 0.6 g/100 g (dw) for F. vesiculosus and C. tomentosum, respectively.…”
Section: Chemical Characterization Of Seaweedssupporting
confidence: 91%
See 1 more Smart Citation
“…The lipid and ash content of F. vesiculosus and C. tomentosum agree generally with that described in the literature [56,[58][59][60][61]. The lipid content found in this work was 3.4 ± 0.5 and 2.2 ± 0.6 g/100 g (dw) for F. vesiculosus and C. tomentosum, respectively.…”
Section: Chemical Characterization Of Seaweedssupporting
confidence: 91%
“…The protein content is known to be higher in green and red seaweeds (10-47% dw) than in brown seaweeds (5-24% dw) [2]. The protein content found for F. vesiculosus is within the range observed by other authors [57,60,61]. On the other hand, C. tomentosum showed a relatively higher protein content than that reported in some studies [62,63], but similar to that obtained by Rodrigues et al [56].…”
Section: Chemical Characterization Of Seaweedssupporting
confidence: 85%
“…However, this level is not always exceeded by Ulva spp. in Swedish waters, as has been previously shown (Olsson, Toth, & Albers, 2020a), and factors influencing fluctuations of such metal content in biomass require further investigation. It has been previously shown that so-called "heavy metals" can influence the thickness of the cell wall in U. intestinalis (Zeroual et al, 2020).…”
Section: Discussionmentioning
confidence: 76%
“…Seaweed extracts are organic and biodegradable substances and are considered an important source of nutrition in sustainable agriculture [ 16 ]. There are numerous seaweed species, with more than 10,000 red, brown and green seaweed species [ 17 ]. Some brown seaweed species are used more frequently, such as Ascophyllum nodosum (L.) Le Jol., Ecklonia maxima , Macrocystis pyrifera and Durvillea potatorum [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous seaweed species, with more than 10,000 red, brown and green seaweed species [ 17 ]. Some brown seaweed species are used more frequently, such as Ascophyllum nodosum (L.) Le Jol., Ecklonia maxima , Macrocystis pyrifera and Durvillea potatorum [ 17 ]. According to Metting et al [ 18 ], plants that are treated with seaweed extracts had increased crop yield, nutrition uptake, seed germination and postharvest shelf-life, and they were also resistant to stress conditions, such as high temperature or frost, and less susceptible to insect attacks and fungal infections.…”
Section: Introductionmentioning
confidence: 99%